Eve-teasing detection from video footage using computer vision and artificial intelligence - Rapheo, Abdullah; Billah, A.T.M. Masum; Islam, Lamisha; MD Yahia Mahim, Abu Shale (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2023.